GENETIC CHARACTERIZATION OF FARMED AND WILD POPULATIONS OF AFRICAN CATFISH (Clarias gariepinus BURCHELL, 1822) THROUGH RANDOM AMPLIFIED POLYMORPHIC MARKER - SULEIMAN, SAADU BALA (Journal of Agricultural Sciences (Belgrade), 2020)
Abstract: Genetic characterization of Clarias gariepinus was conducted in this study. Thirty (30) Clarias gariepinus samples were collected, fifteen (15) each from wild and farms in Northeast Nigeria for their genetic relatedness and diversity using RAPD marker. DNA extraction from the blood sample was performed using Gene Jet Genomic DNA Purification Kit.  OPB10, OPB12, OPB20, OPE08 and OPE18 are the primers used and amplified using PCR. A total of 402 RAPD bands were amplified by the five primers from the four strains of Clarias gariepinus. Three hundred and six (76.12%) bands were polymorphic while the remaining 86 (21.39%) were found to be monomorphic. Percentage polymorphism obtained by each population (farmed and wild) ranged from 58 (47.3%) to 69 (75.9%) respectively. The polymorphic bands per loci within the populations ranged from 67.9% to 82.0%. The mean numbers of inbreeding coefficient (FIS) was 0.083 in farmed population and 0.053 in wild population. Total gene diversity estimated within farmed and wild populations (Ht) was 0.4522 and 0.4018 respectively. The mean genetic differentiation (FST) values in the populations range between (0.203) in farmed and 0.129 in wild. The Analysis of Molecular Variance (AMOVA) revealed that there is 96% genetic molecular variance within the population which is an indication of 4% genetic variability among the population. Nei's unbiased analysis of genetic identity and genetic distance of four populations were found to be 0.9490 and 0.1038 respectively. The phylogenetic measure has shown that the four (4) strains were divided into two (2) clusters at approximately 0.089 similarity levels. The result indicated significant level of genetic variation and minimal dendrogram separation in Clarias gariepinus in Northeastern Nigeria. In conclusion, this information will be a useful tool for genetic identification and breeding program in Clarias gariepinus as a marker assisted selection to improve the fish growth performance.